Involvement of Toll Like Receptor 2 Signaling in Secondary Injury during Experimental Diffuse Axonal Injury in Rats - Yonglin Zhao; Junjie Zhao; Ming Zhang; Yahui Zhao; Jiaxi Li; Xudong Ma; Tingqin Huang; Honggang Pang; Bo Wang; Jinning Song (Hindawi Limited, 2017)
Treatment of diffuse axonal injury (DAI) remains challenging in clinical practice due to the unclear pathophysiological mechanism. Uncontrolled, excessive inflammation is one of the most recognized mechanisms that contribute to the secondary injury after DAI. Toll like receptor 2 (TLR2) is highlighted for the initiation of a vicious self-propagating inflammatory circle. However, the role and detailed mechanism of TLR2 in secondary injury is yet mostly unknown. In this study, we demonstrated the expression of TLR2 levels in cortex, corpus callosum, and internal capsule and the localization of TLR2 in neurons and glial cells in rat DAI models. Intracerebral knockdown of TLR2 significantly downregulated TLR2 expression, attenuated cortical apoptosis, lessened glial response, and reduced the secondary axonal and neuronal injury in the cortex by inhibiting phosphorylation of mitogen-activated protein kinases (MAPK) including Erk, JNK, and p38, translocation of NF-κB p65 from the cytoplasm to the nucleus, and decreasing levels of proinflammatory cytokines including interleukin-6, interleukin-1β, and tumor necrosis factor-α. On the contrary, administration of TLR2 agonist to DAI rats achieved an opposite effect. Collectively, we demonstrated that TLR2 was involved in mediating secondary injury after DAI by inducing inflammation via the MAPK and NF-κB pathways.